Good Governance in Climate Change Policy Towards Net Zero Emission Through Renewable Energy Project - Nicken Sarwo Rini; Josua Hari; Netty S.R. Naiborhu; Nanda Vico Saeful Hakim (Universitas Airlangga, 2026)
Based on Paris Agreement, states should comply to control climate change and energy policy needs to be adjusted. Developed country uses absolute basin and carbon intensity approach in climate change mitigation but Indonesia still uses business as usual in current condition. Energy sector, primarily the current policy needs to be reviewed in order to achieve Nationally Determined Contribution (NDC). This article uses doctrinal method that focused on policy review in energy sector with statutory approach, also comparative approach between The Netherlands and China compare to Indonesia strategy towards national determined contribution in climate change, and conceptual approach to achieve net zero emission by developing renewable energy project. Dependency in fossil fuel has a major contribution in current Indonesia energy policy. Coal dominating in economic sector by stakeholders and it is shown the needs of coal is high in industry. It makes the energy transition by renewable energy project is still left behind. The article limits the analysis in just energy transition through policy in a legal framework. Authors find out that legal policy creates fundamental energy transition in renewable energy project for making sustainable development in environmental, economy, and social pillars. Transformative legal policy is important in energy transition to fulfill national determined contribution towards net zero emission. Designing adaptive regulatory is the key to mitigate climate change via eco-friendly power plant construction.